(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
g vowels, consonants, stress, and intonation patterns. Understanding these differences is crucial for learners of English in Uzbekistan, as phonetic interference often leads to pronunciation errors. By comparing key phonetic features, this paper aims to help language learners and teachers recognize potential difficulties and develop effective pronunciation strategies. The findings emphasize that awareness of articulatory distinctions and practice through phonetic training can significantly improve communication skills and language fluency.